A Hybrid Electrochemical Energy Storage Device Using Sustainable Electrode Materials. Issue 4 (30th January 2020) - Minakshi, Manickam; Mitchell, David R. G.; Jones, Robert T.; Pramanik, Nimai Chand; Jean‐Fulcrand, Annelise; Garnweitner, Georg
Abstract: A new electrochemical energy storage device, comprising a faradaic rechargeable pseudo‐capacitor type electrode with a non‐faradaic rechargeable capacitor electrode, is successfully developed for potential applications in smart electric grids. Mapping new electrodes possessing both high energy and power densities as well as long cycle life is vital for the sustainable energy management. In this work, we present a new approach to design electrodes, fabricated from sustainable resources by hybridizing calcined eggshell capacitor anode with a mixed binary metal oxide pseudo‐capacitor cathode. Calcium carbonate (calcite), obtained from the biowaste‐derived eggshell, is an effective electrode material and operates via accumulation of ions on the electrode surface, providing a high discharge capacitance of 100 F/g through a non‐faradaic process. The calcite present in eggshells is found to be a valuable renewable resource which can be utilized for energy storage through suitable process design. Otherwise, such potentially useful materials (eggshells) are generally discarded as landfill. The mixed binary metallic oxide (NiO/Co3 O4 ) showed a typical pseudocapacitive behaviour associated with both charge transfer reactions and electrostatic means provided a high discharge capacitance of 225 F/g. The fabricated prototype hybrid device provides an energy density 35 Wh/Kg at a power density 420 W/Kg. The charge storage characteristics of the hybrid device depend heavily on the current rate employed. The design and fabrication of new sustainable electrode materials provides an understanding of materials and their electrochemical performance in the high‐voltage window. Abstract : Electrochemical energy storage device, comprising a faradaic rechargeable pseudo‐capacitor type electrode with a non‐faradaic rechargeable capacitor electrode, is successfully developed. In this work, we present a new approach to design electrodes, fabricated from sustainable resources by hybridizing calcined eggshell capacitor anode with a mixed binary metal oxide pseudo‐capacitor cathode.